Investigating associations between hearing, cognition, and social isolation using the Hertfordshire Ageing Study - Dhanda, Nisha; Hall, Amanda; Martin, James; Pryce, Helen (Frontiers in Public Health, 2025)
ObjectivesThe aim of the study was to investigate whether hearing threshold separately predicts cognitive score and social isolation score 10 years later by using the Hertfordshire Ageing Study (HAS) data.MethodsThe Hertfordshire Ageing Study (HAS) is a longitudinal cohort study that measures hearing via pure tone audiometry at two timepoints, and social isolation and cognition variables at the second timepoint. Linear regression was implemented for both objectives using an unadjusted model, a model controlling for age and gender, and a model controlling for all confounders (sociodemographic, lifestyle, and clinical characteristics) relating to the exposure and outcome variables. For interpretability, coefficients were expressed as the expected change in outcome per doubling of hearing threshold.ResultsA total of 231 and 254 participants were included in the final analyses. Over 10 years, hearing thresholds worsened by an average of 10.5 dB. Higher hearing thresholds were associated with lower MMSE scores (β per doubling of hearing = −1.02, 95% CI –2.07–0.03) and with lower social isolation scores (β per doubling = −0.37, 95% CI –1.40–0.66). Although these associations were not statistically significant, the confidence intervals suggest that small but potentially meaningful effects cannot be excluded.ConclusionThe lack of evidence of an association despite strong theoretical evidence may be due to selection bias within the overall cohort study and the sensitivity of the outcome measures used for social isolation and cognition.